Potential of video games in learning Bahasa Melayu vocabulary among international university students in Malaysia: a meta analysis of selected journals - Rosman, Fuziah; Alias, Norlidah; Siraj, Saedah; Kenatullah, Husaina Banu; Zakaria, Abdul Razak; Darusalam , Ghazali (TOJET, 2013)
This study uses a meta analysis to analyze several current articles published by selected journals by focusing on studies related to the potential of video games in Bahasa Melayu vocabulary learning by international students. Among the articles are those in journals such as Computers and Education, Computers in Human Behavior, Education Technology Research Development, Procedia Social and Behavioral Sciences, Australian Journal of Language and Literacy, Computer Assisted Language Learning, Educational Technology & Society, and Scandinavian Journal of Educational Research published between 2003 and 2011. For this study, only 15 articles were focused on out of 33 articles in journals published between 2003 until 2011. Nevertheless, only 9 articles were identified using the key words video games and language learning. In terms of methodology, most of the articles were literature reviews followed by case studies and experimental studies. Some articles combined quantitative and qualitative approaches. Findings from all the articles reviewed show that video games have potential as effective teaching aids and are capable of motivating students in language learning.